Literary Text in Time and Space - Tatiana N. Fedulenkova (Вестник Северного (Арктического) федерального университета: Серия «Гуманитарные и социальные науки»)
Review of the book: Lunkova L.N. Worlds and Spaces of a Literary Text. Moscow, 2020. 160 p.